2006
DOI: 10.1159/000097896
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Thymidine Phosphorylase Expression at the Invasive Front of T3 Rectal Cancer as a Prognostic Factor

Abstract: Purpose: Vascular endothelial growth factor (VEGF) and thymidine phosphorylase (TP) are angiogenic factors. We evaluated the relationship between the degree of expression of binary angiogenic factors and the malignant potential of colorectal cancer. Methods: This study was conducted in 61 patients with T3 rectal cancer who underwent surgical curative resection between 1998 and 2002. Paraffin-embedded sections of their surgical specimens were immunostained for VEGF and TP. The relationship between the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A high VEGF expression level is considered to be a prognostic factor of colorectal cancer, particularly in patients exhibiting lymph node metastasis. Previous studies have reported significant correlations between clinicopathologic features and TP expression levels ( 19 , 35 , 37 ), whereas other studies have reported an inverse correlation between the TP expression level and lymph node/hematogenous metastasis ( 22 ); thus, the association between TP expression level and clinicopathologic features is considered to be controversial ( 23 , 37 41 ). It was hypothesized in the current study that the significance of the TP expression levels is minimal with regard to angiogenesis (which is assessed by MVD), when high VEGF expression levels are sufficient to induce VEGF-associated angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high VEGF expression level is considered to be a prognostic factor of colorectal cancer, particularly in patients exhibiting lymph node metastasis. Previous studies have reported significant correlations between clinicopathologic features and TP expression levels ( 19 , 35 , 37 ), whereas other studies have reported an inverse correlation between the TP expression level and lymph node/hematogenous metastasis ( 22 ); thus, the association between TP expression level and clinicopathologic features is considered to be controversial ( 23 , 37 41 ). It was hypothesized in the current study that the significance of the TP expression levels is minimal with regard to angiogenesis (which is assessed by MVD), when high VEGF expression levels are sufficient to induce VEGF-associated angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, various reports regarding colorectal cancer specified that VEGF expression was closely correlated with tumor angiogenesis ( 11 , 12 , 32 ), and may be considered an independent prognostic factor ( 1 , 7 , 33 ), while a study indicated that there was no apparent correlations ( 12 ). In addition, previous reports analyzed the positive correlations between a high VEGF expression level and lymph node metastasis ( 1 , 34 ), while certain studies revealed negative correlations ( 35 , 36 ). In the present study, MVD in the high VEGF expression group was observed to be significantly higher than that of the low VEGF expression group, and patients' overall survival rate in the high VEGF expression group tended to be lower when compared with that of the low VEGF expression group.…”
Section: Discussionmentioning
confidence: 99%
“…Logistic regression analysis is used when the dependent variable is dichotomous or nominal, in which case the explanatory variables can be numerical, ordinal, or nominal. Multivariable logistic regression analysis has been widely used for prediction 1,2 and diagnosis 3 . References 1 and 2 are only two examples of recent studies dealing with colorectal cancer.…”
Section: Multivariable Logistic Regression Analysismentioning
confidence: 99%